Enhancing Education Through Online Project-Based Learning (PBL): Strategies, Challenges, and Outcomes in the Digital Era - Syaikhu, Ahmad (EDUCATIO : Journal of Education, 2024)
This study explores the application of Online Project-Based Learning (PBL) as an innovative pedagogical model designed to enhance student engagement and skill development in the digital era. With the rise of information and communication technologies, Online PBL has emerged as a flexible and accessible alternative to traditional learning methods. This research examines various online PBL models implemented in educational settings, focusing on platforms like Learning Management Systems (LMS), social media integration, and online collaboration tools such as Google Workspace and Microsoft Teams. The findings highlight the benefits of these models in fostering critical thinking, collaboration, and technological proficiency. However, the study also identifies challenges such as limited access to technology, the lack of face-to-face interaction, and difficulties in assessing student performance. The paper concludes with recommendations for overcoming these challenges, including teacher training, improved technological infrastructure, and curriculum adjustments to support the successful integration of online PBL. The implications for future educational practices and the continued evolution of PBL in digital learning environments are discussed.